PERLINDUNGAN HUKUM BAGI PEKERJA MIGRAN INDONESIA DI PROVINSI NUSA TENGGARA BARAT - Yanto, Edi; Aminwara, Rena; Sahrul (Faculty of Law, University of Mataram, 2023)
The purpose of this study, as described by the author, can be summarized as follows: first, to obtain a comprehensive understanding of the legal Forms of Protection for Indonesian Migrant Workers (PMI); second, to gain a complete picture of the role of the Regional Government of the Province of West Nusa Tenggara in the Placement and Protection of Indonesian Migrant Workers (PMI). This type of research is normative and empirical legal research, which examines legal materials and data. The approach used is a combination of a statutory approach and a sociological approach, followed by a qualitative descriptive analysis. Forms of Protection for Indonesian Migrant Workers (PMI) in positive law are regulated in Law Number 18 of 2017 concerning the Protection of Indonesian Migrant Workers and Government Regulation Number 59 of 2021 concerning the Protection of Indonesian Migrant Workers. Where the forms of protection include protection before work, during work, and after work. The Role of the Regional Government of the Province of West Nusa Tenggara in the Placement and Protection of Indonesian Migrant Workers (PMI). In general, the implementation is carried out jointly between the central government and regional governments, including P3MI, in accordance with their duties and authorities. The West Nusa Tenggara Regional Government has implemented a policy in the West Governor's Regulation concerning the establishment of P3MI branch offices. Where is the local government authorized to organize job education and training, manage the return of workers in the event of a problem according to their authority, issue P3MI branch office permits, set up assistance posts and services at places of departure and return, supervise the implementation of Placement of Indonesian Migrant Workers, and establish LTSA (One-Stop Integrated Service).